HAK PASIEN ATAS REKAM MEDIS PADA PERJANJIAN TERAPEUTIK DALAM PERSPEKTIF HUKUM PERIKATAN - Ziaul Arvan (2023)
The medical record is an important thing that contains the patient's track record from the beginning of treatment. The medical record is also a record to evaluate the progress of the patient's condition during treatment which can be used as written evidence. Patients and doctors in health practice have an interrelated relationship, so that it will give birth to rights and obligations for both parties. In the medical record as evidence of the occurrence of therapeutic transactions between doctors and patients Juridically, a therapeutic contract includes the type of endeavor agreement (inspanings verbintenis). And based on Article 1233 of the Civil Code it states that each engagement can be born either because of an agreement or because of a law. If we look at the relationship between patient and doctor, in this case, of course, the relationship that occurs is an engagement relationship, moreover theoretically it fulfills the requirements for the engagement relationship category. If the engagement relationship is of course doctors and patients have the same rights and obligations over medical records, in reality patients do not get this Medical Record that makes a sense of unfairness to patients. The purpose of this research is to find out the ownership status of medical records associated with ownership rights for patients and to find out whether the transactions that occur between doctors and patients constitute an agreement.